Early Treatment With a Single Dose of Mesenchymal Stem Cell Derived Extracellular Vesicles Modulates the Brain Transcriptome to Create Neuroprotective Changes in a Porcine Model of Traumatic Brain Injury and Hemorrhagic Shock. Issue 2 (17th November 2021) - Bambakidis, Ted; Dekker, Simone E.; Williams, Aaron M.; Biesterveld, Ben E.; Bhatti, Umar F.; Liu, Baoling; Li, Yongqing; Pickell, Zachary; Buller, Benjamin; Alam, Hasan B.
ABSTRACT: Background: Cell-based therapies using mesenchymal stem cell derived extracellular vesicles (EVs) improve neurologic outcomes in animal models of traumatic brain injury (TBI), stroke, and hemorrhage. Using a porcine 7-day survival model of TBI and hemorrhagic shock (HS), we previously demonstrated that EV-treatment was associated with reduced brain lesion size, neurologic severity score, and cerebral inflammation. However, the underlying cellular and genomic mechanisms remain poorly defined. We hypothesize that EV treatment modulates the brain transcriptome to enhance neuroprotection and neurorestoration following TBI + HS. Methods: Swine were subjected to severe TBI (8-mm cortical impact) and HS (40% blood volume). After 1 h of shock, animals were randomized (n = 4/group) to treatment with either lactated Ringer's (LR) or LR + EV. Both groups received fluid resuscitation after 2 h of shock, and autologous packed red blood cells 5 h later. After 7-days, brains were harvested and RNA-sequencing was performed. The transcriptomic data were imported into the iPathway pipeline for bioinformatics analyses. Results: 5, 273 genes were differentially expressed in the LR + EV group versus LR alone (total 9, 588 measured genes). Genes with the greatest upregulation were involved in synaptic transmission and neuronal development and differentiation, while downregulated genes were involved in inflammation. GO-terms experiencing the greatest modulation were involved in inflammation, brain development, and cell adhesion. Pathway analysis revealed significant modulation in the glutamatergic and GABAergic systems. Network analysis revealed downregulation of inflammation, and upregulation of neurogenesis, and neuron survival and differentiation. Conclusions: In a porcine model of TBI + HS, EV treatment was associated with an attenuation of cerebral inflammatory networks and a promotion of neurogenesis and neuroplasticity. These transcriptomic changes could explain the observed neuroprotective and neurorestorative properties associated with EV treatment.